Menjejak Sejarah di Linggarjati: Museum, Saksi Bisu Perundingan yang Melahirkan Kemerdekaan - Sri Rumiati; Nurhawanih Nurhawanih; Fitri Hayati; Elly Rasimah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the historical background, process, and significance of the Linggarjati Agreement and its relevance to education and nationalism. The research employed a descriptive qualitative approach using historical research methods. Data were collected through library research, documentation studies, and direct field observation at the Linggarjati Museum in Kuningan, West Java, on February 14, 2026. Data analysis was conducted through heuristic, source verification, interpretation, and historiography stages. The findings indicate that the Linggarjati Agreement represented a realistic diplomatic strategy undertaken by the Indonesian government to maintain sovereignty after independence. The agreement served as an initial step toward de facto international recognition of the Republic of Indonesia. Beyond its historical significance, the Linggarjati Museum also holds educational value as a contextual learning resource that fosters nationalism, dialogue, and peaceful conflict resolution. Therefore, Linggarjati is not merely a historical symbol but also a strategic medium for strengthening character education and national awareness among the younger generation.